FA’ĀLIYAH WASĪLAH AL-KALIMĀT AL-MUTAQĀṬI‘AH LI SAIṬARAH AT-ṬULLĀB ‘ALA FAHM AN-NAṢ AL-‘ARABI FĪ SMP IT MADRASAHATUL QUR’AN ACEH BESAR - Mukhlisah, Mukhlisah; Nurrahmi, Nurrahmi; Adhim, Said Kasyful (Islam Futura, 2022)
SMP IT Madrasatul Quran is one of the Islamic boarding schools that offer Arabic as a second language programs in the everyday school environment. This also includes memorizing verses of the Qur'an and studying Arabic for eighteen hours a week at school. They also learn to speak and understand Arabic scripts. This process is a good effort to improve students' ability and understanding of Arabic texts. But in reality, most of the students face difficulty in understanding the Arabic language, especially in understanding the text because they find it difficult to memorize the vocabulary and they have a lack of vocabulary, and this makes them weak in understanding and speaking the Arabic language. Therefore, the researcher wanted to conduct a research entitled: "The Effectiveness of the Crossword Tool in Improving Students' Understanding of the Arabic Text in SMP IT Madrasatul Quran". The aim of this research is to improve the students' ability to understand the Arabic text and know their response to the use of crossword puzzles. The method of research in this research is Classroom action research. The research was conducted on eighth grade students of the SMP IT Madrasatul Quran. The research tools used are the questionnaire and the test. The result shows that the application of the crossword puzzle is effective in improving the students' understanding of the Arabic text with the mean score 86.16, and the students respond positively with the mean score 3.64. In addition, the use of the crossword puzzle helps in motivating the students and their interest in learning and understanding the Arabic text better than before